Analysis of Indexes of the Russian Bank Cards Market by Various Criteria - E. V. Lapteva (Статистика и экономика)
Purpose of the study. The article presents the results of a study and analysis of the performance indexes of the Russian bank cards market on various grounds, because bank cards contribute to increasing the availability of financial services. Having a bank card allows you to carry out financial transactions anytime and anywhere and makes these transactions more convenient and transparent. The use of bank cards as a non-cash form of payment is not only convenient and practical, but also contributes to improving the economic situation in the country, expanding the availability of financial services and improving financial literacy.Materials and methods. As research tools, such methods were used as: analysis of the structure and dynamics of the main indexes, correlation and regression analysis, analysis of time series and forecasting, graphical and tabular methods for presenting research results.Results. The analysis carried out in relation to the issue of bank cards in Russia made it possible to establish the impact on the number of payment cards of two factors: the number of credit institutions and the average per capita income of the population (per month). The results obtained showed that an increase in the number of credit institutions leads to a reduction in the number of issued payment cards. In turn, with an increase in the average per capita monetary income of the population (per month), the number of payment cards increases. This suggests that a high level of income and good conditions for obtaining credit funds are an incentive to use payment cards. Bank cards are an integral part of the financial services market. The development of the bank card market has an impact on stimulating the country’s economic growth and improving the quality of life of the population. In modern conditions, banks are actively introducing electronic technologies and improving the use of bank cards by customers. The creation of convenient services and the introduction of new technologies make it possible to expand the possibilities of using bank cards for their holders.